What Matters Make Kilinochchi Paddy Cultivators to Thrive? - Umashankar, K.; Luxan, M. (Sri Lanka Agricultural Economics Association, 2016)
Besides being a part of the household diet in Sri Lanka rice is the staple food and, the highest cultivated crop in Sri Lanka. Thus elevation of resilience is both theoretically and practically the most consistent and comprehensive proposal for the survival of the community through the risk and uncertainty. However, a number of socio-economic factors together determine the resilience of a farm household. Hence, the researchers have taken an effort to assess the paddy farmers' resilience together with the major objectives to (i). Find out the determinants of resilience of paddy farmers in Kilinochchi district and (ii). Propose policy recommendations to strengthen the resilience of paddy farmers in the above district. Primary data were collected randomly from 169 paddy cultivators. Structural equation model was used to analyze the resilience with livelihood approach. The results revealed that the five endogenous latent variables namely food access, assets, social safety net, adaptive capacity, stability and access to public services have excreted positive significant effect on the resilience of paddy farmers. The resulted second level of interactions between endogenous latent variable and the measurable variables revealed that food access score, dietary diversity index, land ownership, agricultural asset index, employment ratio, coping strategy index, education system stability, educational level of household head, distance to input market revealed a significant positive effect on the resilience while frequency of assistance and dietary energy consumption revealed a significant negative effect on the resilience of paddy farmers of the districts.
Keywords: Food security; Resilience; Paddy farmers; Structural Equation Model; Sri Lanka